The benefits of steroid as therapy for tuberculous effusion - Barmawi Hisyam Barmawi Hisyam (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2001)
Tuberculous effusion is a complication of pulmonary or extra pulmonary tuberculosis. The specific diagnosis is made by the finding of mycobacterium in the effusion and pleural tissue. Therapy of tuberculous effusion is mainly reducing symptoms, prevent progressivity and fibrothorax. Common complications of tuberculous effusion are pleural fibrosis, thickening and calcification of pleura. To prevent those, corticosteroid is often needed as additional therapy, besides anti tuberculous drugs. There has been controversy about the benefits of steroid as therapy for tuberculous effusion.Keywords : pulmonary tuberculosis, extrapulmonary tuberculosis, tuberculous effusion, corticosteroids, anti tuberculous drugs.,